2011
DOI: 10.1270/jsbbs.61.121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a wheat transcription factor, TaWRKY45, and its effect on Fusarium head blight resistance in transgenic wheat plants

Abstract: The WRKY transcription factors belong to a large protein family characterized by the conserved WRKY domain. These factors have been identified to play biological functions in various plant developmental processes. WRKY proteins are also known to be involved in regulating plant responses to pathogen attack and stressrelated hormones. In this study, we report the isolation and characterization of the gene (TaWRKY45) for the wheat WRKY45 transcription factor. Amino acid sequence alignment and phylogenetic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…In the present study, LR treatment induced the expression of four WRKY transcription factors in KU-2084, namely WRKY24 (homolg of TaWRKY41), WRKY62 (homlog of Tawrky15), WRKY70 (homolog of TaWRKY 45), and WRKY72 (homolog of TaWRKY19). As TaWRKY45 reportedly enhances transgenic wheat resistance to Fusarium head bright [23] and several WRKY members are involved in PAMP recognition of pathogen threat in plants [8,37], the upregulation of these WRKY genes in infected KU-2084 may represent a mechanism of either plant-pathogenic response or pathogenic defense.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, LR treatment induced the expression of four WRKY transcription factors in KU-2084, namely WRKY24 (homolg of TaWRKY41), WRKY62 (homlog of Tawrky15), WRKY70 (homolog of TaWRKY 45), and WRKY72 (homolog of TaWRKY19). As TaWRKY45 reportedly enhances transgenic wheat resistance to Fusarium head bright [23] and several WRKY members are involved in PAMP recognition of pathogen threat in plants [8,37], the upregulation of these WRKY genes in infected KU-2084 may represent a mechanism of either plant-pathogenic response or pathogenic defense.…”
Section: Discussionmentioning
confidence: 99%
“…More and more results demonstrated that over-expression of stress responsive transcription factors is a promising strategy for improving abiotic stress tolerance in crop [26,27]. Some members of WRKY family have been found to be responsive to various abiotic stresses [28].…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY transcription factors have been known in the regulation of transcriptional reprogramming associated with plant immune responses [ 70 , 71 ]. The constitutive overexpression of WRKY conferred an enhanced resistance against F. graminearum in transgenic wheat plants grown under greenhouse conditions [ 72 ]. The TaWRKY70 from wheat acts as a positive regulator of resistance against F. graminearum [ 73 ].…”
Section: Discussionmentioning
confidence: 99%